Key Drivers of Sustainability Practices in the UK Banking Sector: implications for Sustainable Development Goals - Ekene Ekemezie; Kaodilichukwu Augustine Echem (Journal of Gender and Millennium Development Studies, 2025)
Background: This study investigates the key drivers influencing sustainability practices in the UK banking sector amid increasing global expectations aligned with the Sustainable Development Goals (SDGs). Objective: To explore stakeholder perceptions regarding banks’ sustainability efforts. Method: A quantitative research design was employed using an online survey administered to 191 randomly selected respondents from a population of 2.5 million stakeholders, including bank executives, employees, customers, investors, regulators, and advocacy groups. Data were collected through structured questionnaires and analyzed using descriptive statistics and t-tests. Results: The findings indicate that community engagement, corporate social responsibility, credible sustainability reporting, and financial performance significantly influence stakeholder perceptions. Conversely, transparency in reporting was not widely perceived as impactful. T-test results revealed no statistically significant factors, thereby supporting the null hypothesis. Conclusion: While UK banks exhibit alignment with SDGs 8, 9, 11, 12, 13, and 16, weak governmental influence underscores the need for stronger policy frameworks and intersectoral collaboration. Contribution: The study highlights the importance of enhancing stakeholder education and integrating environmental, social, and governance (ESG) principles into core banking strategies and operations.